Analisa Pengaruh Desain Kumparan 6-Fasa Terhadap Efisiensi Motor Induksi 3-Fasa Menggunakan Metode Ganda Tak Simetris - Ririn Devilani; Zuriman Anthony; Erhaneli Erhaneli (STEKOM PRESS, 2024)
This research aims to analyze the impact of a new coil winding design in 3-phase induction motor on effiiciency, with the objective of creating a new 3-phase induction motor with improved performance. The research was conducted in the Electric Power System Laboratority, Department of Electrical Engineering, Padang Institute of Technology, and focuses solely on efficiency and its relationship to motor output power. The study involved redesigning the coils of a conventional 3-phase induction motor into a 6-phase coil design without altering the motor’s position, followed by testing both motors and comparing the efficiency of the conventional 3-phase induction motor with that of the redesigned 6-phase motor using the asymmetrical double methode. The result show that the efficiency of the 6-phase coil-designed motor increased compared to the conventional 3-phase induction motor. importance of maintaining data security and implementing AI strategically to provide optimal benefits for consumers and business development.